The effectiveness of loyalty card toward customers loyalty. a case study: Aeon Bandaraya Melaka / Siti Nur Amalina Mohd Zayadi and Nur Aryanni Mohd Fauzy Yeo - Mohd Zayadi, Siti Nur Amalina; Mohd Fauzy Yeo, Nur Aryanni (2015)
This paper is to examine the effectiveness of loyalty card toward customer loyalty in AEON Bandaraya Melaka. Besides, there is specific study about the effectiveness of loyalty card toward customer loyalty in AEON Bandaraya Melaka where mostly previous study is about the general effectiveness of loyalty card toward customer loyalty. Thus, the theoretical framework was done from the previous journal. With a convenience sampling method used in this research, about 108 questionnaire distributed to the customers before the result have revealed relationship and significant of conceptual framework of this topic. Particularly, the four conceptual factors which are trust, satisfaction, attitude, commitment and loyalty card has been analyzed. Then, the result of the study would indicate the effectiveness of loyalty card toward customer loyalty in AEON Bandaraya Melaka.